2018
DOI: 10.1155/2018/6524945
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of Wind Pressure Coefficients on C-Shaped Building Models

Abstract: Designs of buildings are changing with emerging demands of several aesthetical features and efficient design based on geometry. Development of new building materials and construction techniques have enabled us to build new buildings which are tall and unsymmetrical, but unfortunately such structures are more susceptible to wind loads. Thus it becomes necessary to estimate wind loads with higher degree of confidence. Although ample information regarding wind load on symmetrical and regular structure is availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 23 publications
(24 reference statements)
0
7
0
2
Order By: Relevance
“…Similar pressure coefficient (C p ) is observed in the windward faces for the levels of height h/6 and h/2, whereas a mild deviation is observed leeward faces for the levels h/6 and h/2 respectively. On the contrary, for the top height 4.15h/5 experiences a huge negative pressure coefficient (C p ) for the faces G and H. Table 6 shows the error analysis for R 2 Previous researcher [27] have carried out error analysis by comparing a wind tunnel and CFD results for the building of C-plan shape building and rectangular building with an opening. Table 6 displays the error analysis for the present study using R 2 , ME, RMSE and MAPE.…”
Section: Angle Of Incidence -90˚mentioning
confidence: 99%
“…Similar pressure coefficient (C p ) is observed in the windward faces for the levels of height h/6 and h/2, whereas a mild deviation is observed leeward faces for the levels h/6 and h/2 respectively. On the contrary, for the top height 4.15h/5 experiences a huge negative pressure coefficient (C p ) for the faces G and H. Table 6 shows the error analysis for R 2 Previous researcher [27] have carried out error analysis by comparing a wind tunnel and CFD results for the building of C-plan shape building and rectangular building with an opening. Table 6 displays the error analysis for the present study using R 2 , ME, RMSE and MAPE.…”
Section: Angle Of Incidence -90˚mentioning
confidence: 99%
“…Ma [12] proposed the wind pressure extremum algorithm combining the experimental data with numerical simulation. Malick et al [13] put forward the wind pressure coefficient model of "C" planshaped tall building model and process of obtaining its solution. Quan et al [14] proposed a wind pressure extreme value estimation method based on generalized extreme value theory.…”
Section: Introductionmentioning
confidence: 99%
“…They proposed an empirical formulation by considering the side ratio and territory of the building to express wind load. Mallick et al [22] reported the experimental wind tunnel and numerical studies on distribution of pressure coefficient on curved surfaces of C-shaped building model.…”
Section: Introductionmentioning
confidence: 99%